2016
DOI: 10.1016/j.tube.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 and the Mycobacterium tuberculosis granuloma: A systematic review and meta-analysis

Abstract: Infection with HIV-1 greatly increases the risk of active tuberculosis (TB). Although hypotheses suggest HIV-1 disrupts Mycobacterium tuberculosis (Mtb) granuloma function, few studies have examined this directly. The objective of this study was to determine what evidence exists about the effect HIV-1 co-infection has upon Mtb granulomas. A systematic search of PubMed, Web of Science, and Medline up to 20 March 2015 was conducted, to identify studies comparing Mtb-infected tissue from HIV-1 infected and uninfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 63 publications
1
55
2
1
Order By: Relevance
“…HIV infection has also been shown in vitro to increase the growth of M. tuberculosis in coinfected macrophages [10, 11], but such responses are highly variable [12]. Although these studies demonstrate that HIV causes specific reductions in the immunological responses to M. tuberculosis , very few studies have clearly demonstrated how HIV changes these responses within granulomas [13], the archetypal microscopic hallmark of tuberculosis-diseased tissue. The immunological function and cellular composition of granulomas significantly varies between granulomas [14] and blood or airways [15], demonstrating the need to examine granulomas directly [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HIV infection has also been shown in vitro to increase the growth of M. tuberculosis in coinfected macrophages [10, 11], but such responses are highly variable [12]. Although these studies demonstrate that HIV causes specific reductions in the immunological responses to M. tuberculosis , very few studies have clearly demonstrated how HIV changes these responses within granulomas [13], the archetypal microscopic hallmark of tuberculosis-diseased tissue. The immunological function and cellular composition of granulomas significantly varies between granulomas [14] and blood or airways [15], demonstrating the need to examine granulomas directly [16].…”
mentioning
confidence: 99%
“…Studies that have examined granulomas in persons with HIV and M. tuberculosis coinfection (hereafter, “coninfected persons”) and those with M. tuberculosis monoinfection are highly variable, and it is difficult to draw firm conclusions about how HIV changes granuloma organization, formation, cellular composition, and M. tuberculosis abundance [13]. The inconsistency of these data partially results from the highly variable and heterogeneous nature of granulomas, a limited number of studies, a low number of persons in the studies, and highly variable and qualitative methods, which make comparisons among multiple studies difficult.…”
mentioning
confidence: 99%
“…This is supported by data showing that reductions in CD4+ counts in co-infected persons were associated with both poorer granuloma formation and higher bacterial load. [14] …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HIV impairs the TNF-α mediated apoptosis of mφ, and thus facilitates the survival of bacilli. Moreover, HIV disintegrates the granuloma organization leading to dissemination of bacilli [49].…”
Section: Macrophagesmentioning
confidence: 99%